Algal cell bionics as a step towards photosynthesis-independent hydrogen production - Zhijun Xu; Jiarui Qi; Shengliang Wang; Xiaoman Liu; Mei Li; Stephen Mann; Xin Huang (Nature Communications, 2023)
Low rate and limited duration are major challenges in photobiological hydrogen production. Here, the authors coat algal cells with a concentrically arranged shell comprising an ultra-thin Fe(III)-doped polypyrrole inner layer and outer exoskeleton of CaCO3, and achieve sustainable H2 production for over 200 days.